HUBUNGAN SIKAP ANGKAT DAN FREKUENSI ANGKUT DENGAN KELUHAN NYERI PINGGANG PADA TENAGA KERJA PENGANGKUT BERAS DI GUDANG BULOG 402 SOKARAJA KABUPATEN BANYUMAS - Dwi Bayu Retnaningtyas; Siti Harwanti; Nur Ulfah (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2013)
ABSTRACTCarrier rice laborer is an informal sector worker who works to transfer the rice sacks from the truck load to the rice storehouse, they carried it with their waist or back. Transferring goods manually will build the lifting posture and hauling frequencies. Unnatural lifting postures will potentially be led to low back pain that marked by pain complaints. Low back pain is a pain on the lumbosacral and sacroiliac area that followed by the pain spreading from the leg to the foot. A mechanical factor is one of the main causes of low back pain from the heavy and repetitive activities. The pain characteristics were preceded by the hefty goods lifting history and the unnatural bending position while lifting the weighty goods. The purposed of this research was to understand the correlation of lifting postures and hauling frequencies that could cause low back pain. The type of this research was an observational analytic research with a crossectional technique. There were a total of 40 samples that had taken with the Total Population Technique from the Bulog 402 Storehouse Sokaraja. The data collected with the Skala Analogue scale (SAV) for low back pain. Data that had been collected were analyzed with the Rank Spearman correlation test. The Rank Spearman test results showed, that there was a correlation between lifting postures with low back pain, (p =0.016): (α=<0.05) and Correction Correlation (CC) = 0.380*. Meanwhile, there was no correlation between the hauling frequencies with low back pain. We recommended that the Bulog 402 storehouse management should conduct a regular supervision on their laborer work posture during their work time, and for the laborer it selves, a correct working posture and lifting goods with the suitable weight can reduce low back pain incidents. Keyword : Postures, Frequencies, Low Back Pain Kesmasindo Volume 6, (2)Juli 2013, Hal 143-149